Citizenship education in Turkey from militant-secular to Islamic nationalism - Sen, Abdulkerim (Lexington Books, 2020)
This book is a critical investigation of the curriculum change in citizenship education in Turkey from 1995 to 2012. Relying on interviews and policy documents, it draws on the conventions of critical discourse analysis and provides a comprehensive account of the ideological evolution of the citizenship education curriculum.